Risk in virtual organisation: a case study. (1st January 2012) - Alawamleh, Mohammad; Popplewell, Keith
The environment within which SMEs have to function in the 21st century is one that is increasingly competitive and dynamic and therefore, simply to cope in such a situation, SMEs have to seek for a number of methods to employ and one of these is to group together within a virtual organisation (VO). It is, however, not easy to become part of a VO and there are risks to be dealt with throughout the whole process from the initial formation of such a group through to the point where it dissolves. In order that the challenges can be met successfully, it is important that enterprises should be helped to both recognise the risks and then surmount them. Based on case study, this paper aims to develop a deeper understanding of the main constructs of risk sources in VOs, especially their dependencies and perceptions.